2002
DOI: 10.1002/chin.200220061
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Resolution of (RS)‐Proglumide Using Lipase from Candida cylindraceae.

Abstract: 2002 carboxylic amides carboxylic amides (benzene compounds) Q 0490 -061Resolution of (RS)-Proglumide Using Lipase from Candida cylindraceae.--(MURALIDHAR, R. V.; CHIRUMAMILLA, R. R.; RAMACHANDRAN, V. N.; MARCHANT, R.; NIGAM, P.; Bioorg. Med.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…A smaller P value means the corresponding coefficient is more significant (Muralidhar et al . ). The concentration of Ca(OH) 2 solution was the most significant ( P value = 0.0006) factor affecting the yield of SRBF and the concentration of Ca(OH) 2 solution on the effect of SRBF yield analysis exhibited the largest linear regression coefficient (0.38; Table ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…A smaller P value means the corresponding coefficient is more significant (Muralidhar et al . ). The concentration of Ca(OH) 2 solution was the most significant ( P value = 0.0006) factor affecting the yield of SRBF and the concentration of Ca(OH) 2 solution on the effect of SRBF yield analysis exhibited the largest linear regression coefficient (0.38; Table ).…”
Section: Resultsmentioning
confidence: 97%
“…In addition, Muralidhar et al . () have reported that a circular contour plot can be used to demonstrate insignificant interactions between the corresponding variables and an elliptical contour plot demonstrates significant interactions between corresponding variables. Therefore, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The P value is used as a tool to check the significance of each coefficient and the interaction strength between each independent variable [22]. According to the P values of each model term summarized in Table 2, it could be concluded that these terms including an independent variable ( X 2 ) and two quadratic terms ( X 1 2 and X 2 2 ) were significantly affecting the yield of gentisides (“Prob > F ” less than 0.05), and among them quadratic terms were the most significant parameters which influenced GY.…”
Section: Resultsmentioning
confidence: 99%
“…According to contour plots' shapes produced by Design-Expert 8.0.6., response surface plots demonstrated whether the mutual interactions between the variables are significant or not, which were shown in Figure 4. Circular contour plot indicates that the interactions between the corresponding variables are negligible, while elliptical contour plot indicates that the interactions between the corresponding variables are significant [22]. As two variables were depicted in same plots while the other variable was kept at level 0, relationships between independent and dependent variables could be intuitively conveyed.…”
Section: Resultsmentioning
confidence: 99%